TIPOLOGI KAWASAN BERISIKO BANJIR DI DAERAH ALIRAN SUNGAI (DAS) KALI PEPE, KOTA SURAKARTA - Nur Miladan; Kusumaningdyah Nurul Handayani; Dewa Putu Aris Sadana (TATALOKA, 2018)
Flooding is the most dominant disaster in the world and it takes place until recently. So far, the urban flood reduction is carried out through the structural and non structural mitigation approaches. The spatial mitigation approach is very needed to be considered in the flood risk management besides those approaches. The spatial transformation (land use pattern), and environmental carrying capacity can be used to realize the spatial approach in disaster risk management. This research aims to analyze the flood risk area typology in Kali Pepe River Basin, Surakarta City. It uses deductive approach with quantitative methods being supported by spatial analysis. The results indicate there are 42 spatial types, but only 18 types being the flood risk areas. Land caracteristic tends to be not correlated to the flood impact intensity. Land use pattern and drainage caracteristics have a tendency to be correlated to the flood impact risk. The spatial planning could be focused on urban settlements, especially in areas with high building densities. The built-up space restrictions should be implemented in the river sourrounding areas, and the infrastructure engineering concern with the river upstream-downstream system.